The Triple Dusk-Dawn Aberration of the Solar Wind at Earth - Borovsky, Joseph E. (Frontiers in Astronomy and Space Sciences, 2022)
In this Brief Report it is pointed out that there are 3 dusk-dawn aberrations of the solar-wind plasma and magnetic structure approaching Earth and the magnitudes of these aberrations are estimated for various solar-wind types monitored from L1. Solar-wind monitors closer to the Earth than L1 would have superior performances.